Analisis Pemanfaatan Keberadaan Micro Influencer dalam Strategi Media Sosial Instagram sebagai Strategi Pendekatan ke Audiens di Era Digital - Chaniago, Hanifa Zahra; Majid, Nurkholish (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research employs a qualitative methodology with a constructivist paradigm approach to comprehend the cultural significance of social media. The study is primarily descriptive, seeking to depict how social media has emerged as the predominant platform for individuals to receive information, share content, engage in interpersonal aspects of their lives, and acquire knowledge about the surrounding world. Utilizing qualitative methods, this investigation delves into perceptions, experiences, and social constructions associated with social media usage in society. The findings offer profound insights into the role and influence of social media within the audience framework during the digital era. Drawing from the research findings on the three influencers, namely @mahesaputriadriano, @cindyosmann, and @gabrielangelica, it can be concluded that by effectively employing algorithms and strategies, social media exerts a significant impact on enhancing brand awareness, user engagement, and purchase conversions, as supported by research and studies. Keywords: influencer, mikro influencer, media sosial, public relations